Niddah, Immersion, and the Mikveh in Jewish-Feminist Art: Between Israel and the United States - Sperber, David (Mabatim: Journal of Visual Culture, 2022)
The transgression of taboos concerning women’s bodies and sexuality was widespread in the works of American feminist artists of the 1970s. A particular strand of this engagement focuses on niddah (menstrual separation), ritual immersion, and the mikveh. This article examines artistic works that address the laws and rituals of niddah and immersion and discusses the differences between artistic production on this subject in the two major Jewish centers – the United States and Israel. To this end, the article analyzes the works of two leading artists in this field: Hagit Molgan in Israel (b. 1972) and Mierle Laderman Ukeles in the United States (b. 1939). Although both were raised within Modern Orthodox society and continue to identify with it today, their approaches to the laws of niddah differ fundamentally. Examining the differences between their works, their reception, and the interpretive discourse surrounding them, in light of the distinct strands of Jewish feminism, and comparing them to additional works by Jewish women artists active in these contexts, contributes to a more nuanced understanding of the environments in which this art is produced, as well as of the similarities and divergences across cultural spaces. While scholarship on feminist thought, activism, and art is well developed, religious feminist art has not yet been thoroughly studied. An investigation of feminist art that explicitly engages with religious subjects refines our understanding of its unique contribution to both the art world and the feminist movement within which these artists operate.